INFORMATION DIGITALIZATION, CORPORATE SOCIAL RESPONSIBILITY AND ITS EFFECT ON FIRM VALUE - Suci Safitri; Wirmie Eka Putra; Fitrini Mansur (Universitas Airlangga, 2023)
The main objective of this research is to analyze the effect of the levelof information on digitization and corporate social responsibility tofirm values. Studies on property and real estate sector companieslisted on the IDX for the 2019-2021 period. This type of research isquantitative research. The sampling technique used purposivelysampling method and obtained a sample of 39 companies. this studyuse secondary data such as the annual report and sustainability report.The data analysis method in this study used multiple regressionanalysis using SPSS version 26. The results showed that the level ofinformation digitalization and corporate social responsibility partiallyhad influences to firm values. Companies in the property and realthe estate sector in Indonesia can use CSR disclosure as a means toincrease firm value. However, the level of information digitizationhas not been able to positively influence firm values becausedisclosure of digitized information in the property and real estate sectorcompanies are still low